Analisis Pengaruh Ekspor, Impor, Nilai Tukar, dan Inflasi terhadap Cadangan Devisa Indonesia Tahun 1996-2020 - Dinda AB Permana; Sitti Retno Faridatussalam (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
This study aims to analyze the effect of imports, exports, inflation, and exchange rates with Indonesia's foreign exchange reserves simultaneously and partially with a time limit of 1996-2020. This study utilizes secondary data, namely time series data with a period of 25 years. Linear regression is an analytical method used in this study with the Partial Adjustment Model (PAM) approach. The results of this study indicate that there is a positive and significant influence that exists between exports and foreign exchange reserves and there is no significant effect between the research variables.